(S)-1-(Ethoxycarbonyl)ethyl(2R,5S)-2,5-dimethyl-1,3-dioxolan-4-one-2-carboxylate - R. Alan Aitken; Oliver E. Haslett; Alexandra M. Z. Slawin (Molbank, 2021)
The title compound was obtained in low yield in the condensation of ethyl pyruvate and lactic acid. Its structure is determined by NMR methods and x-ray diffraction and the mechanism for formation of this 1:2 adduct from the initial 1:1 adduct is considered.